EWSR1::SMAD3-rearranged fibroblastic tumor: A case with twice recurrence and literature review - Yang, Li; Fan, Linni; Yin, Zhiyong; Liu, Yixiong; Zhao, Danhui; Wang, Zhe; Cheng, Hong (Frontiers in Oncology, 2022)
EWSR1::SMAD3 rearranged fibroblastic tumor is a recently described entity that mostly occurs in acral locations. Only 15 cases have been reported in the English literature, with a wide age range and marked female predominance. The most common sites are the foot, followed by the hand and the distal lower leg. There are 4 cases recurred locally during 5-120 months follow-up, with no metastases to date. Herein, we present a case of EWSR1::SMAD3 rearranged fibroblastic tumor that recurred twice in a 20-year-old man. The patient presented with a second recurrent painful nodule in the left plantar of the second toe. Grossly, the lesion was pale solid and well-defined measuring 9×8×9mm in size. Histological examination revealed a monomorphic spindle cell tumor composed of cellular fascicles of bland fibroblasts in a collagenous to myxoid stroma with low mitotic activity, which evoked a wide spectrum of differential diagnoses. Immunohistochemically, the tumor cells were diffusely and strongly positive for ERG, while negative for S100, α-SMA, CD34 and other vascular markers. An unbalanced rearrangement of EWSR1 was demonstrated by fluorescence in situ hybridization (FISH), and a gene fusion between EWSR1 exon7 and SMAD3 exon6 was confirmed by RT-PCR and Sanger sequencing. This case recurred twice within six years with no sign of further relapse and metastasis at another 9-month follow-up since the last surgery, indicating this tumor was benign but prone to local recurrence. Nevertheless, more cases and further studies are needed to better interpret the biological behavior of this new entity.